واقع حرائق بعض الغابات في محافظة اللاذقية وسبل تجديدها (Latakia University Journal -Biological Sciences Series, 2018)
تتعرض غابات محافظة اللاذقية سنويا إلى الحرائق وتدل الإحصائيات على أن عددها قد ازداد في السنوات الأخيرة، حيث وصلت إلى /110/ حرائق في العام /2004/، وقد تفاوتت المساحات المتضررة من الحرائق بين المساحات الصغيرة التي تراوحت بين بضعة عشرات أو مئات من الأمتار المربعة وبضعة عشرات من الدونمات. أما في الفترة الواقعة بين مطلع الثمانينات ومنتصف التسعينات من القرن الماضي فكان عدد الحرائق أقل مما ذكر ولكن المساحات المحروقة كانت أكبر بكثير حيث وصلت إلى بضعة آلاف من الدونمات كما حدث عام /1985/ في بعض المناطق مثل قسطل المعاف /3500/ دونم، وفي منطقة وادي قنديل عام /1991/ حيث بلغت المساحة المحروقة /5500/ دونم. من خلال دراسة المواقع المعتمدة في هذا البحث تبيّن أن غالبيتها لم تستثمر لأغراض أخرى (زراعية أو أبنية. ..الخ.)  وإنما تركت لتتجدد طبيعيا بواسطة البذور المتوفرة وبشكل بطيء أو تم تحريجها بالصنوبر الثمري (.Pinus pinea L) والخرنوب(Ceratonia siliqua L.) كعامل يساعد على عدم التعرض لها من جديد كون هذه النباتات ذات مستقبل اقتصادي.   The forests in Lattakia Governorate are exposed to fires every year. Statistics indicate that their number has increased in recent years and reached /110 / fires in 2004. The areas damaged from the fires varied between the small areas which ranged between several tens or hundreds of square meters, and several tens of hectares. While in the early eighties and mid nineties, the number of fires was less than that mentioned above, but the areas burned were much larger, where they reached several thousands of hectares; this is what happened in 1985 in some districts such as Kastal Almouaaf /3500/ hectares. And the area burned in Wadi Kandil district in 1991 reached /5500/ hectares. By studying the locations specified in this paper, we have shown that most of them were not exploited for other purposes (farming or building, etc.) but left to renew naturally and slowly through the available seeds, or they were afforestated with Pinus pinea L. and Ceratonia siliqua L. being a factor that helps prevent them being damaged again, since such plants have an economic future.